Soil physical attributes under grazing intensities and methods with lambs on integrated crop‑livestock systems - Carassai, Igor Justin; Carvalho, Paulo César de Faccio; Cardoso, Raquel Rolim; Flores, João Paulo Cassol; Anghinoni, Ibanor; Nabinger, Carlos; de Freitas, Fabiana Kellermann; Macari, Stefani; Trein, Carlos Ricardo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate possible alterations in the soil bulk density and total porosity due to lamb trampling, under different grazing management after no-tillage summer crop. The experiment was carried out in the layers 0–2.5, 2.5–5 e 5–10 cm of an arenic Ultisol, in an annual ryegrass pasture with forage allowance of 2.5 and 5.0 of animal potential consumption, under continuous and rotational stocking. An ungrazed area was used as check. Grazing intensities and methods did not affect soil bulk density and total porosity. It is possible to use areas with this kind of soil texture, with cover crops for lamb grazing in the winter, without alterations on soil physical attributes, caused by animal trampling, reach harmful levels for subsequent crops.